Green adhesives : preparation, properties and applications - Inamuddin, 1980-; Boddula, Rajender; Ahamed, Mohd Imran; Asiri, Abdullah M. (John Wiley & Sons, Inc., 2020)
"Synthetic adhesives are known for their toxic impact on the natural environment. In the emerging scientific world, many challenges are arising in the industrial sectors as a consequence of trying to meet the demands posed by upgraded technologies. The development of green adhesives based on renewable resources is the necessity of this age. Their importance is growing gradually as the commercial market is motivated to emphasize the benefits of green adhesives. Green adhesives, particularly those based on polysaccharides, have a number of good features, like biodegradability, biocompatibility, bio-inertness, antimicrobial activity, nontoxicity, and low cost, that keep pace with synthetic adhesives"--